2021
DOI: 10.1038/s41467-021-21382-2
|View full text |Cite
|
Sign up to set email alerts
|

The TUTase URT1 connects decapping activators and prevents the accumulation of excessively deadenylated mRNAs to avoid siRNA biogenesis

Abstract: Uridylation is a widespread modification destabilizing eukaryotic mRNAs. Yet, molecular mechanisms underlying TUTase-mediated mRNA degradation remain mostly unresolved. Here, we report that the Arabidopsis TUTase URT1 participates in a molecular network connecting several translational repressors/decapping activators. URT1 directly interacts with DECAPPING 5 (DCP5), the Arabidopsis ortholog of human LSM14 and yeast Scd6, and this interaction connects URT1 to additional decay factors like DDX6/Dhh1-like RNA hel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 76 publications
2
42
0
Order By: Relevance
“…The pPABP2-PABP2-RFP reporter lines in wild-type and hsp101 background were described in Merret et al (2017). The pUBQ-DCP5-GFP like was a kind gift from the laboratory of Scheer, Hélène (Scheer et al, 2021) while the hsp101 mutant and complementation line used for the germination phenotypes of Supporting Information Fig. S5 (see later) were a kind gift from Elizabeth Vierling (McLoughlin et al, 2019).…”
Section: Plant Materialsmentioning
confidence: 99%
“…The pPABP2-PABP2-RFP reporter lines in wild-type and hsp101 background were described in Merret et al (2017). The pUBQ-DCP5-GFP like was a kind gift from the laboratory of Scheer, Hélène (Scheer et al, 2021) while the hsp101 mutant and complementation line used for the germination phenotypes of Supporting Information Fig. S5 (see later) were a kind gift from Elizabeth Vierling (McLoughlin et al, 2019).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Important roles for this new regulation layer were identified in specific processes like antiviral response [8], transposon control [9], germline development [10,11], or RNA degradation triggered by apoptosis [12]. Still, the significance of pervasive mRNA uridylation in the context of bulk mRNA turnover is unclear, and elimination of uridylation generates no detectable consequences for the physiology of somatic cells and only limited molecular manifestations [7,11,13].…”
Section: Introductionmentioning
confidence: 99%
“…We validated the siRNA counting function using publicly available datasets from Scheer et al (2021). This study sequenced sRNAs from wildtype and three mutant strains of Arabidopsis and identified siRNAs within those four datasets.…”
Section: Resultsmentioning
confidence: 99%
“…2012, Wei et al . 2019, Rogers and Phillips 2020, Scheer et al . 2021), or (ii) identifying subsets of siRNAs by immunoprecipitating a specific Argonaute protein and recovering associated sRNAs (e.g., Claycomb et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation